Analysis of the Interpretation of Article XI GATT in the Case Study of Indonesia’s Nickel Ore Export Ban, WTO Case No. DS592 - Talitha, Raisyha; Nurkhaerani, Ema (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the interpretation of GATT 1994 Article XI by the WTO Panel in the DS592 dispute (Indonesia—Measures Relating to Raw Materials) concerning Indonesia's nickel ore export ban. This policy is deemed to violate the fundamental principle of GATT Article XI:1 on the absolute prohibition of quantitative restrictions. The research utilizes a normative legal research method with case and statutory approaches. The conclusion shows that the WTO Panel factually determined the export ban violates GATT Article XI:1. The Panel rejected all of Indonesia's justification arguments (Article XI:2(a) and Article XX(d)) due to a strict interpretation and Indonesia’s failure to prove the absolute ban was a